Peran Satuan Polisi Pamong Praja Dalam Penyelenggaraan Ketertiban Umum Dan Ketenteraman Masyarakat Di Kota Surabaya - Ilmiyah, Muidatin; Wahyudi, Kalvin Edo (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The author's purpose in this study is to describe the role of the Civil Service Police Unit in the implementation of public order and public peace in the city of Surabaya, based on how the problem has been formulated. So in this study researchers used a qualitative approach with descriptive objectives which included four research focuses, namely early detection and prevention, coaching and counseling, patrolling, and control. As much as possible, Satpol PP Surabaya City has taken a number of steps to maintain peace and order in the city of Surabaya. Satpol PP Surabaya City has begun to carry out coaching and counseling activities as well as enforcement of jurisdiction and non-jurisdiction. Another effort is to create a work schedule that is suitable for the organization and adopt a humanist attitude towards the residents of Surabaya City.